Performance Evaluation of Certified Teachers Towards Professional Teachers at SMA Negeri 2 Seram Barat - Fera Tohatta; R. Kempa; A. Sahalessy (Peneliti.net, 2022)
Teachers as educators have a very important role in the progress of the Indonesian nation, teachers are also one of the determining factors for the success of education. Educational staff, especially teachers, are the soul of the school, therefore increasing the personalism of education personnel starts from needs analysis, planning, development, performance evaluation, and work relations. The work performance produced by these teachers is the result of the leadership of the principal as the leader of an educational institution who always moves, directs, and motivates teachers to be serious in carrying out their duties in order to achieve the goals that have been set together. This research is based on the problem of how the performance of certified teachers at SMA Negeri 2 Seram Barat is. Operationally, the objectives of this study are (1) to evaluate the performance of certified teachers in the aspect of pedagogic competence. (2) Evaluating the performance of certified teachers in the aspect of professional competence. (3) Evaluating the performance of certified teachers in the aspect of personality competence. (4) Evaluating the performance of certified teachers in the aspect of social competence. The type of research used is evaluation research using a qualitative descriptive approach, namely research that aims to describe the situation comprehensively in the real context. In this case, to collect information about the evaluation of learning programs at SMA Negeri 2 Seram Barat, then use that information as the basis or basis for making policies or decisions about quality school programs. The results of the evaluation of the performance of certified teachers at SMA Negeri 2 Seram Barat, namely teaching and learning activities are the main activities that are always carried out by certified teachers, at SMA Negeri 2 Seram Barat. Schools are given the freedom to choose effective learning and teaching strategies, methods and techniques, according to the characteristics of subjects, students, teachers and the real conditions of the resources available in the school. For learning planning, it starts with mapping basic competencies and indicators, compiling syllabus, compiling lesson plans, compiling annual programs, preparing semester programs, and then the result of the planning is a pattern regarding teaching programs that will be used in the learning process in the classroom. In relation to the 4 competencies that a certified teacher must possess, namely; pedagogic competence, professional competence, personality competence and social competence. Basically, teachers of SMA Negeri 2 Seram Barat have pedagogic, professional, personality and social competencies.